Q: How do you get to 24 by using 7 3 5 6?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Yes. 6*(5 - 3)*2 = 6*2*2 = 12*2 = 24

(7+6-5) x 3 = 8 x 3 = 24

By using: (3*6)+(3*2) = 24

2*(5-3)*6 = 24

It is: 6*(5-2)+6 = 24.

Related questions

8 x 3 x (6 - 5) = 24 6 x 8 ÷ (5 - 3) = 24

5+3=8 8-4=4 4*6=24

Yes. 6*(5 - 3)*2 = 6*2*2 = 12*2 = 24

54 divided by 3 is equal to 18. 18+6 is equal to 24.

One way is (5 - 3)*sqrt(4)*6

(7+6-5) x 3 = 8 x 3 = 24

common denominator is going to be 24 8=222 6=2*3 24=222*3 8 should be multiplied by 3 6 should be multiplied by 4 5/6=(5*4)/(6*4)=20/24 7/8=21/24 5/6=20/24```

By using: (3*6)+(3*2) = 24

Multiply 6 and 4. Multiply 8 and 3.

ok 6 divided by 2 is 3 3 times 5 is 15 15 plus 9 is 24 :D

(3 + 5 - 6) × 12 = 24.

2*(5-3)*6 = 24